Different bulk and active bacterial communities in cryoconite from the margin and interior of the Greenland ice sheet. Issue 2 (23rd January 2015) - Stibal, Marek; Schostag, Morten; Cameron, Karen A.; Hansen, Lars H.; Chandler, David M.; Wadham, Jemma L.; Jacobsen, Carsten S.
Summary Biological processes in the supraglacial ecosystem, including cryoconite, contribute to nutrient cycling within the cryosphere and may affect surface melting, yet little is known of the diversity of the active microbes in these environments. We examined the bacterial abundance and community composition of cryoconite over a melt season at two contrasting sites at the margin and in the interior of the Greenland ice sheet, using sequence analysis and quantitative polymerase chain reaction of coextracted 16S rDNA and rRNA. Significant differences were found between bulk (rDNA) and potentially active (rRNA) communities, and between communities sampled from the two sites. Higher concentrations of rRNA than rDNA were detected at the interior site, whereas at the margin several orders of magnitude less rRNA was found compared with rDNA, which may be explained by a lower proportion of active bacteria at the margin site. The rRNA communities at both sites were dominated by a few taxa of Cyanobacteria and Alpha‐ and/or Betaproteobacteria. The bulk alpha diversity was higher in the margin site community, suggesting that local sources may be contributing towards the gene pool in addition to long distance transport.